Performance Audit and the New Public Management (NPM) Reforms: Addressing the Public Sector Inefficiency in Nigeria - Abubakar, Abdulkadir; Saidin, Siti Zabedah; Ahmi, Aidi (School of Social Sciences, USM, 2017)
With the advent of NPM in the public sector, the auditing profession has been elaborately transformed to include many other classes of audit. NPM has been a guiding public sector reform template for over 25 years. Performance audit is one of the audit exercises promoted by the NPM regime. Over the years, the emphasis on 3Es (efficiency, effectiveness and economy) has necessitated the government agencies in many countries around the globe to bring government activities under meticulous scrutiny. Thus, performance audit is a formal tool for evaluating 3Es in the public sector by ensuring that, conformity and compliance with the principles and procedures of the public governance are adequately guaranteed. Specifically, the performance audit practice is at the infant stage in Nigeria. Hence, public agencies that adopted the performance audit are poised to face unanticipated challenges. Therefore, driving from that emphasis, this study presents a multi-level experience of OECD countries on the performance audit. Explicitly, this study is a conceptual review of views and experiences of the OECD countries on the impact of the performance audit with regards to NPM reforms. Equally, the study also reflects on the consensus that, 3Es determines the public sector organizational performance.